1997
DOI: 10.1177/096032719701600809
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase status, pharmacokinetics and laboratory findings during obidoxime therapy in organophosphate poisoned patients

Abstract: 1 The effectiveness of oxime therapy in organophos phate poisoning is still a matter of debate. It appears, however, that the often cited ineffectiveness of oximes may be due to inappropriate dosing. By virtue of in vitro findings and theoretical considerations we concluded in the preceding paper that oximes should preferably be administered by continuous infusion following an initial bolus dose for as long as reactiva tion of inhibited acetylcholinesterase (AChE) can be expected. This conclusion has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 16 publications
2
78
0
2
Order By: Relevance
“…Moreover, enormous differences between species have to be considered (12). Based on reaction constants derived from experiments with human RBC-AChE, reasonable plasma concentrations of oximes for reactivation of insecticide as well as nerve agentinhibited AChE can be calculated (2,11,(13)(14)(15)(16)(17)(18)(19). Results indicate that AChE inhibited by most nerve agents and insecticide OPs can be reactivated with obidoxime at a plasma concentration of approximately 10 µmol L -1 .…”
Section: Reactivation Of Acetylcholinesterasementioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, enormous differences between species have to be considered (12). Based on reaction constants derived from experiments with human RBC-AChE, reasonable plasma concentrations of oximes for reactivation of insecticide as well as nerve agentinhibited AChE can be calculated (2,11,(13)(14)(15)(16)(17)(18)(19). Results indicate that AChE inhibited by most nerve agents and insecticide OPs can be reactivated with obidoxime at a plasma concentration of approximately 10 µmol L -1 .…”
Section: Reactivation Of Acetylcholinesterasementioning
confidence: 97%
“…bolus dose of 250 mg, followed by 750 mg of obidoxime per day. In actual emergency situations, this regimen proved effective in reactivating AChE inhibited by insecticide OP (11,16,20).…”
Section: Reactivation Of Acetylcholinesterasementioning
confidence: 99%
See 1 more Smart Citation
“…The obidoxime treatment of OPP poisoned patients was better reported. The combined obidoxime-atropine treatment was effective in patients poisoned by smaller doses of parathion, while the poisoning by the high dose of parathion was not successfully reactivated until parathion levels declined (Thiermann 1997). In the same study, obidoxime was reported as ineffective for oxydemetonmethyl poisoning, but the time elapsed between ingestion and oxime therapy was longer than one day (Thiermann 1997).…”
Section: Trimedoxime and Obidoximementioning
confidence: 99%
“…The combined obidoxime-atropine treatment was effective in patients poisoned by smaller doses of parathion, while the poisoning by the high dose of parathion was not successfully reactivated until parathion levels declined (Thiermann 1997). In the same study, obidoxime was reported as ineffective for oxydemetonmethyl poisoning, but the time elapsed between ingestion and oxime therapy was longer than one day (Thiermann 1997). The enzyme-based assay for quantification of paraoxon in blood of parathion poisoned patients confirmed significant obidoxime reactivation of low plasma paraoxon concentration, whilst diethylphosphoryloxime formation during obidoxime-induced reactivation did not markedly contribute to the reinhibition of AChE (Eyer 1998).…”
Section: Trimedoxime and Obidoximementioning
confidence: 99%